Evaluation of a serological test for tuberculosis. Issue 6073 (28th May 1977) - Mitchison, D A; Aber, V R; Ahmad, F J; Allen, B W; Devi, S
Abstract : The agglutination test of Nicholls was found to be ineffective in diagnosing active tuberculosis. A positive result (titre of 1/125 or more) was found in the serum of 74 (70%) out of 105 patients with newly diagnosed, smear-positive pulmonary tuberculosis; 61 (62%) out of 98 healthy family contacts; and 19 (63%) out of 30 patients with non-tuberculous conditions. These findings were not due to faulty technique since the results obtained at Hammersmith were similar to those obtained by Nicholls's laboratory in the same serum samples. Twenty-seven of the tuberculous patients who had a negative result before treatment were retested two months after the start of chemotherapy but showed no evidence of a rising titre.